Flocculation of dimorphic yeast benjaminiella poitrasii is altered by modulation of NAD-glutamate dehydrogenase - Joshi, C. V.; Ghormade, Vandana; Kunde, P.; Kulkarni, P.; Mamgain, H.; Bhat, Suresh K.; Paknikar, K. M.; Deshpande, Mukund V. (Bioresource Technology, 2010)
A strategy to control flocculation is investigated using dimorphic yeast, Benjaminiella poitrasii as a model. Parent form of this yeast (Y) exhibited faster flocculation (11.1 min) than the monomorphic yeast form mutant Y-5 (12.6 min). Atomic force microscopy revealed higher surface roughness of Y (439.34 rms) than Y-5 (52 rms). Also, the former had a zeta potential of -65.97 +/- 3.45 as against -50.21 +/- 2.49 for the latter. Flocculation of both Y and Y-5 could be altered by supplementing either substrates or inhibitor of NAD-glutamate dehydrogenase (NAD-GDH) in the growth media. The rate of flocculation was promoted by alpha-ketoglutarate or isophthalic acid and decelerated by glutamate with a statistically significant inverse correlation to corresponding NAD-GDH levels. These interesting findings open up new possibilities of using NAD-GDH modulating agents to control flocculation in fermentations for easier downstream processing. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Benjaminiella poitrasii; dimorphism; flocculation; NAD-glutamate dehydrogenase

Molecular studies of NAD- and NADP-glutamate dehydrogenases decipher the conundrum of yeast-hypha dimorphism in zygomycete Benjaminiella poitrasii - Pathan, Ejaj K.; Ghormade, Vandana; Panwar, Sneh Lata; Prasad, Rajendra; Deshpande, Mukund V. (Fems Yeast Research, 2019)
Benjaminiella poitrasii, a zygomycete, shows glucose- and temperature-dependent yeast (Y)-hypha (H) dimorphic transition. Earlier, we reported the biochemical correlation of relative proportion of NAD- and NADP-glutamate dehydrogenases (GDHs) with Y-H transition. Further, we observed the presence of one NAD-GDH and two form-specific NADP-GDH isoenzymes in B. poitrasii. However, molecular studies are necessary to elucidate the explicit role of GDHs in regulating Y-H reversible transition. Here, we report the isolation and characterization of one NAD (BpNADGDH, 2.643 kb) and two separate genes, BpNADPGDH I (Y-form specific, 1.365 kb) and BpNADPGDH II (H-form specific, 1.368 kb) coding for NADP-GDH isoenzymes in B. poitrasii. The transcriptional profiling during Y-H transition showed higher BpNADPGDH I expression in Y cells while expression of BpNADPGDH II was higher in H cells. Moreover, the yeast-form monomorphic mutant (Y-5) did not show BpNADPGDH II expression under normal dimorphism triggering conditions. Transformation with H-form specific BpNADPGDH II induced the germ tube formation in Y-5, which confirmed the cause-effect relationship between BpNADPGDH genes and morphological outcome in B. poitrasii. Interestingly, expression of H-form specific BpNADPGDH II also induced germ tube formation in human pathogenic, non-dimorphic yeast Candida glabrata, which further corroborated our findings.
Keywords: Benjaminiella poitrasii; Candida glabrata; differential gene expression; dimorphism; monomorphic mutant; NAD/NADP-glutamate dehydrogenase; yeast-hypha transition